Recent developments in intergenerational mobility - Sandra E. Black; Paul J. Devereux (Institute for the Study of Labor (IZA), 2010)
Economists and social scientists have long been interested in intergenerational mobility, and documenting the persistence between parents and children's outcomes has been an active area of research. However, since Gary Solon's 1999 Chapter in the Handbook of Labor Economics, the literature has taken an interesting turn. In addition to focusing on obtaining precise estimates of correlations and elasticities, the literature has placed increased emphasis on the causal mechanisms that underlie this relationship. This chapter describes the developments in the intergenerational transmission literature since the 1999 Handbook Chapter. While there have been some important contributions in terms of measurement of elasticities and correlations, we will focus primarily on advances in our understanding of the forces driving the relationship and less on the precision of the correlations themselves.
Keywords: J62; 330; Education; income mobility; income transmission; intergenerational transmission; Soziale Mobilität; Intergenerational Mobility; Generationenbeziehungen; Familiensoziologie; Einkommen; Bildungsniveau